Analysis In-depth People Risk in the Stated Commercial Banks in China and Its Management - ZHU, LI (2013)
When the risk has been occurred in a commercial bank, it will affect the whole banking system. The commercial banks do the well risk precaution to be a significant issue in the society. People is the fundamental element in the development of organizations, in other words, all risks are human risk. Grasping the prevention of people risk means that seize the foundation of bank’s risk. Recently, operational risk brings large amount losses to Chinese state-owned commercial banks. Most of them are from people risk by internal fraud and talent shortage. This paper is to discuss the in-depth people risk in commercial banks, explain the feature of people risk and analyze which management such as operational risk management or human resource management is suitable to prevent and control it.